Transplant Coordinators' Perceived Impact of Availability of Multiple Generic Immunosuppression Therapies on Patients, Workload, and Posttransplant Maintenance Therapy - Parker, K.; Zagadailov, E. A.; Bruno, A. S.; Wiland, A. M. (My University, 2013)
Background. No studies have evaluated the impact of multiple generic immunosuppression medications on transplant coordinators (TCs) and patients. Methods. A cross-sectional, multicenter online survey of TCs managing transplant recipients' outpatient immunosuppression was undertaken to assess TCs' perceptions of the impact of multiple generic immunosuppression therapies on patients and workload. Results. Forty-six of 106 transplant centers contacted (43%) completed the survey, with usable information from 34 TCs (53% in centers performing >100 solid organ transplants annually, 82% registered nurses, and 68% with >5-year experience working with transplant patients). TCs indicated that “change in strength,” “switching from branded to generics,” “heavy pill burden,” and “switching from one generic to another” were the four most frequent reasons for patient confusion regarding immunosuppression. TCs reported increased patient confusion over the previous year for patients on generic immunosuppression therapy: 44% answered ≥3 patient calls/day regarding confusion over immunosuppression therapy. Most TCs indicated increased workload since the introduction of generic immunosuppression therapy. TCs perceived “acute rejection rates,” “rate of graft loss,” and “poor patient adherence” as the three most likely consequences of multiple generic immunosuppression therapy. Conclusion. TCs associated availability of multiple generic immunosuppression therapy with increased patient confusion and time spent addressing patient concerns.